Handbook of seafood and seafood products analysis (CRC Press, 2010)
Handbook of Seafood and Seafood Products Analysis brings together the work of 75 experts who focus on the chemistry and biochemistry of postmortem seafood to offer the very latest methods for testing nutritional and sensory qualities, as well as safety aspects related to processing and preservation of seafood. After providing a general introduction, this handbook offers six sections that detail all areas of consequence to those concerned with delivering quality seafood products: Chemistry and Biochemistry focuses on the analysis of the main chemical and biochemical compounds of seafood; Processing Control describes the analysis of technological quality and includes various methods to differentiate between farmed and wild seafood, to check freshness, and to evaluate smoke flavoring; Nutritional Quality deals with the analysis of nutrients in muscle foods such as essential amino acids, omega fatty acids, antioxidants, vitamins, minerals, and trace elements; Sensory Quality covers the main analytical tools to evaluate color, texture, and flavor; Safety looks at tools used for the detection of pathogens, parasites, viruses, marine toxins, antibiotics, adulterations, and chemical toxic compounds from the environment generated during processing or intentionally added.